Individual investor behaviour: evidence from the clients of a small credit cooperative bank. (23rd January 2012) - Cervellati, Enrico Maria; Fattori, Pino; Pattitoni, Pierpaolo
Individual characteristics are important in explaining investor trading behaviour. The clients of a small cooperative bank are analysed over the three–year period 2005–2007 to measure the effect that age, gender, income, job position and status of online trader has on the number of stock trades completed. A negative binomial regression is used since our dependent variable, the number of trades, can only assume non–negative discrete values. This paper shows that the number of transactions increases if the client is: man vs. women; self–employed vs. employee, retiree or housewife; online vs. traditional trader; higher vs. low income. Our findings are not clear cut with respect to age. In conclusion, individual characteristics are important in explaining an individual's trading behaviour since they affect an investor's attitude towards risk and overconfidence.